2013
DOI: 10.1159/000355508
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Ghrelin Levels in Children before and after Adenoidectomy or Adenotonsillectomy

Abstract: Background and Aim: Accelerated weight gain after (adeno)tonsillectomy has been reported in a number of studies. Whether (adeno)tonsillectomy is also a risk factor for development of overweight is unknown. We investigated serum leptin and plasma ghrelin levels before and 1 year after (adeno)tonsillectomy operation in children. Materials and Methods: We studied 31 patients and 29 age- and sex-matched healthy control children. Auxologic evaluation and biochemical investigations were performed before surgery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(37 reference statements)
2
10
0
Order By: Relevance
“…In addition, subgroup analyses showed a statistically significant BMI z score increase in the intervention group children who were underweight and overweight at baseline compared to the control group. In contrast, the studies conducted by Karalok et al 20 . and Huang et al ., 21 which had longer follow-up times, of 12 months and 3 years respectively, did not show a significant weight gain; therefore, we do not know if this effect is sustained in the long term.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In addition, subgroup analyses showed a statistically significant BMI z score increase in the intervention group children who were underweight and overweight at baseline compared to the control group. In contrast, the studies conducted by Karalok et al 20 . and Huang et al ., 21 which had longer follow-up times, of 12 months and 3 years respectively, did not show a significant weight gain; therefore, we do not know if this effect is sustained in the long term.…”
Section: Discussionmentioning
confidence: 61%
“…studied an underweight cohort with an average BMI z score of less than −1 pre-operatively, 22 whereas the other studies were all within 1 standard deviation pre-operatively. After surgical intervention, the mean BMI of the children had increased in four of the studies to fall into the normal range 20 23 . The study performed by Katz et al .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, OSA also predisposes to the worsening of obesity due to daytime sleepiness, decreased physical activity, and neuroendocrine changes, such as resistance to the anorexigenic hormone leptin;405407 data regarding associations between OSA and levels of the orexigenic hormone ghrelin in children are inconsistent 406,407. Treatment of OSA (primarily T&A, but CPAP in one study) may improve leptin and possibly ghrelin levels, although again, data are somewhat contradictory 407.…”
Section: Obstructive Sleep Apnea and Cardiometabolic Riskmentioning
confidence: 99%
“…The PRISMA flow diagram ( Figure 1 ) summarizes the study screening process. A summary of the studies included in this systematic review and the grading of evidence is reported in Table 1 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%